Penguatan Karakter Islam dalam Pendidikan di Sekolah Madrasah Aliyah Hidayatul Mubtadiin, Kabupaten Lampung Selatan - Cipto Handoko (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Islamic character education aims to continuously shape individual character by fostering the ability to live according to Islamic guidance. This study aims to explore the following aspects: the reinforcement program, the implementation of reinforcement, determining factors in the reinforcement, and the obstacles encountered in strengthening Islamic character education at MA Hidayatul Mubtadiin. This research employs a descriptive method with a qualitative approach. Data collection techniques include observation, interviews, and document analysis. The subjects of the study are the supervisor, principal, and teachers. The findings reveal that: (1) The formulated program is not yet complete or detailed, especially regarding budget allocation for teacher training activities. Nevertheless, the program is implemented as effectively as possible by the principal to strengthen Islamic character education; (2) The program is carried out by involving all school personnel; (3) The principal addresses the determining factors in strengthening Islamic character education through proper monitoring of each programmed activity; and (4) The main obstacle faced is the limited availability of funds for teacher training outside of regular working hours.